Sytuacja kobiet na unijnym rynku pracy - diagnoza stanu - Politaj, Adriana (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Unemployment is still a very big economic and social problem in the Polish economy. Women's situation in labour market in Poland and the European Union is similar. Women are more often unemployed than men. The unemployment rate form women in Poland between 2004 and 2006 was about several percent higher than for men. The problem of women's unemployment accompanies the transformations of the Polish economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 473-480